Penegakan hukum - Al bishri, Siti Khodijah; Amalia, Firda Nur; Rawdak, Zarror Taqi; Maulidy, Muhammad Sabid; Khumairoh, Masitha Hanif (Maliki Interdisciplinary Journal, 2024)
There are many problems still faced by law enforcement in indonesia. Onof the main problems is the discrepancy between the expected legal elements and the actual elements of ilegal application. There are many examples of law enforcement failure to resolve major cases that have not been resolved, such as ongoing corruption. However, cases involing ordinary people show the weakness of other law enforcement. This research investigates the problem of law enforcement in indonesia and discusses the legal structure and system. Descriptive research is the method used. Mandatory law enforcement in indonesia returns to its original goal of creating justice. They still face many problems. One of the main problems is the discrepancy between the expected legal elements and the actual elements of legal application.